Indo-European cooperation in an interdependent world: an overview and analysis - Knall, Bruno; Veit, Wolfgang (Internationales Asien-Forum, 1988)
The authors trace the European Community's (EC) economic relations with India. Bilateral commercial and co-operation agreements between the EC and India. The poor performance of India with respect of her trade with the EC caused by the protectionist policies of the EC and the dirigism in India in the fields of trade, industry and the public sector. India's political relations with Japan, USA, USSR, China and the EC are briefly surveyed. (DÜI-Sen)
Keywords: Europäische Gemeinschaften; Indien